“What support?”: A qualitative study on social support for Asian American victims of racism during the COVID-19 pandemic - Wang, Sherry C.; Santos, Bianca Marie C. (Frontiers in Public Health, 2022)
Since the COVID-19 pandemic, anti-Asian racism has surged, yet little is known about Asian Americans experiences of social support. Therefore, we designed a qualitative, intrinsic, revelatory case study to examine the nature and quality of social support for Asian Americans during the first five months of the pandemic. Our sample consisted of 193 Asian Americans (from over 32 U.S. states) disclosing their experiences of inadequate social support. They described their support network as 1) Being unable to relate, 2) Encouraging their silence, 3) Minimizing anti-Asian racism, 4) Denying anti-Asian racism, and 5) Victim-blaming. Regarding our participants’ recommendations for increasing social support for Asian Americans, a total of seven recommendations emerged: 1) Legitimize anti-Asian racism, 2) Teach Asian American history, 3) Destigmatize mental health resources to make them accessible for Asian American families 4) Promote bystander intervention trainings, 5) Build solidarity with and beyond Asian Americans to dismantle racism, 6) Increase media attention on anti-Asian racism, and 7) Elect political leaders who will advocate for Asian Americans. Altogether, our findings underscore the need for systemic forms of advocacy to combat anti-Asian racism, and shed light on the injurious nature of social support for Asian American victims of racism.